Instilling Civic Disposition Values through Scouting Activities at SMP PAB 9 Klambir Lima Kebun, Deli Serdang - Windawati Pinem; Jamaludin Jamaludin; Muhammad Iqbal; Mazwin Lincah (JED (Jurnal Etika Demokrasi), 2021)
Abstract. The research objective was to analyze how scouting activities in extracurricular programs in junior high schools in instilling civic disposition values, in this case the application of citizen character can be implanted through scouting activities, therefore this study focuses on students who are actively involved in scouting activities. This research method is qualitative using case studies which are the object of research are 10 students, school principals, and scout coaches, the results and conclusions of this research are that every scout activity always uses educational elements, implements a simple lifestyle and a pamong system with scout coaches through expertise. exemplary and civic disposition values from extracurricular activities through scouting activities, there are values of responsibility, discipline, love for the motherland and the environment, tolerance, friendship, honesty, independence, creativity, religion, environmental care and social care.Keywords: Extracurricular, Scouting, Civic DispositionAbstrak.  Tujuan penelitian untuk menganalisis bagaimana kegiatan pramuka pada program ektrakurikuler di sekolah tingkat menengah pertama dalam menanamkan nilai civic disposition, dalam hal ini penerapan watak warganegara apakah dapat ditanamkan melalui kegiatan pramuka, maka dari itu penelitian ini fokus kepada siswa yang terlibat aktif dalam kegiatan kepramukaan. Metode penelitian ini kualitatif dengan menggunakan studi kasus yang menjadi objek penelitiannya adalah 10 orang siswa, kepala sekolah, dan pembina pramuka, hasil dan simpulan penelitian ini yaitu setiap kegiatan pramuka selalu menggunakan unsur pendidikan, menerapkan pola hidup sederhana dan sistem pamong dengan Pembina pramuka melalui kepiawaian teladan dan nilai-nilai Civic disposition dari kegiatan ekstrakurikuler melalui aktivitas pramuka terdapat nilai tanggung jawab, disiplin, cinta tanah air dan lingkungan, toleransi, bersahabat, jujur, mandiri, kreatif, religius, peduli lingkungan dan peduli sosialKata Kunci: Ekstrakurikuler, Pramuka, Civic Disposition.